Pengaruh Kompetensi dan Skeptisme Profesional Terhadap Kualitas Audit - Savira, Jihan Astri; Rahmawati, Rahmawati; Ramadhan, Abid (Institut Bisnis dan Informatika Kesatuan, 2021)
Abstract This study aims to determine and analyze the effect of professional competence and skepticism on audit quality. The population and sample of this study were auditors who worked at the Inspectorate Offices of Luwu Raya (Palopo City, Luwu Regency, North Luwu Regency, East Luwu Regency). The sampling technique used a census technique. The sample in this study was auditors who worked at the Inspectorate Office throughout Luwu Raya. The data collection method used a questionnaire. Kueisoner research uses a Likert scale. Data analysis using multiple linear regression analysis. This research is expected to be used as input and consideration for auditors and as a field of information for further research. The results showed that competence and skepticism had a significant positive effect on auditor quality. Keywords: competency, skepticism, audit quality.